2020
DOI: 10.1142/s1363919620400010
|View full text |Cite
|
Sign up to set email alerts
|

Using Sustainability-Oriented Process Innovation to Shape Product Markets

Abstract: Traditionally, the innovation literature has viewed product innovation as the key competitive driver for firms in the market. But as demands for sustainability increase and technology is advancing sustainability-oriented innovation across industries, there is an opportunity to reconsider the role of process innovations. This study follows the market development process of a start-up founded on the principle of sustainability-oriented innovation and explores how the process innovation itself is used to shape th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…It was found that several firms are combining modular farms with conventional larger scale vertical farms; either starting directly with modular units or starting from larger farms and exploring the use of modular units. Once again, this approach has been highlighted as a way to differentiate from competitors in the market; aligning with previous studies on vertical farm market development, (e.g., Bustamante, 2020). As such, these tailored systems can create customized products to increase competitiveness and a unique profile in the retail market; (see e.g., Pine and Gilmore, 2014;Charters et al, 2017;Jürkenbeck et al, 2019;Sjölander-Lindqvist et al, 2020).…”
Section: Distributed Modular Systemssupporting
confidence: 62%
See 1 more Smart Citation
“…It was found that several firms are combining modular farms with conventional larger scale vertical farms; either starting directly with modular units or starting from larger farms and exploring the use of modular units. Once again, this approach has been highlighted as a way to differentiate from competitors in the market; aligning with previous studies on vertical farm market development, (e.g., Bustamante, 2020). As such, these tailored systems can create customized products to increase competitiveness and a unique profile in the retail market; (see e.g., Pine and Gilmore, 2014;Charters et al, 2017;Jürkenbeck et al, 2019;Sjölander-Lindqvist et al, 2020).…”
Section: Distributed Modular Systemssupporting
confidence: 62%
“…These have spawned from the need to expand their offerings, business models, and connect with consumers in different ways. In recent years, smallscale modular, in-store growing systems are also increasing in popularity and number in connection to residential, commercial, and retail spaces; see also (Bustamante, 2020;Butturini and Marcelis, 2020). These new systems employ new business models for ensuring that customers are provided with fresh plants or tailor-made functions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, higher competitiveness and productivity might be reached via replacing human labour and decision making with robots, automation, or algorithms. This can be a threat to individual freedoms and rights, with implications for societal cohesion, employment, and well-being [35].…”
Section: Sustainability Oriented Innovation: Causes and Effectsmentioning
confidence: 99%
“…The need for innovation in process improvement is crucial when we want to push the limits of the process to a new level. The importance of process innovation is discussed in many sources [7][8][9]. Often, process improvement -or innovation and problem-solving are separated.…”
Section: Introductionmentioning
confidence: 99%